CRASHWORTHINESS ANALYSIS OF ALUMINIUM-COMPOSITE HYBRID CRASH BOX STRUCTURE UNDER QUASI-STATIC AXIAL LOADING - Ghullam Reza A, Muh
The technology development has been recently quite improving, just like transportation industry does. As the transportation technology that continues to grow, people will compete each other in order to fulfil their needs, resulting on the increase of vehicle number on the roads and higher accident potential as well. Many efforts have been carried out to minimize losses due to accidents. One of those studies is focusing on the development of a crashworthy vehicle structure that aims to protect the passengers inside. This research analyses crashworthiness performance of cylindrical aluminium crash box structure and cylindrical aluminium-composite hybrid crash box structure under quasi-static axial loading. The numerical analysis in this research is performed by using LS-DYNA software. There are two parametric studies. The first is conducted to determine the effect of several simulation parameters on the crashworthiness performance and failure mode of the structure. Those parameters which is analysed belong to some parameters of MAT54 (DFAILC, DFAILT, DFAILM, DFAILS, SOFT, and YCFAC), OPTION from tiebreak contact, and some trigger mechanisms. And the second one aims to study the effect of composite ply addition on the crashworthiness performance of aluminium-composite hybrid crash box structure. First parametric study shows that higher DFAILT and DFAILM and lower DFAILC results in higher mean crushing force and absorbed energy. Those parameters also greatly affect the failure mode which occurs on each simulation models as well, if compared with the other MAT54 parameters. Some OPTIONs from tiebreak contact also have huge effect on those two aspects, while the trigger mechanisms only give significant effect on the peak force and failure mode as well. The addition of composite ply number stimulates the increase of mean crushing force and absorbed energy. One ply until six plies model shows the peak force which tends to increase, but on seven plies until nine plies model, that parameter value fluctuates due to the influence of staggered trigger mechanism. The specific energy absorption value tends to decrease on the one ply until four plies model, but on the six plies until nine plies model, that parameter value fluctuates but not too significant.